Evaluation of Retailers Behavior in Forming the Consumer Trend - Shaker, A. (جامعة العلوم والتكنولوجيا – اليمن)
This study aimed to evaluate the behavior of independent retailers in forming the yemeni consumer trend towards concessional domestic goods, the researcher was assumed that each of (the availability of domestic goods in stores), (Advice given by the owner of a retail store to the consumer) and (the attitude of the retailer from the price and the profit) have an impact in forming the consumer trend. To test this assumption, the researcher worked on an Empirical Study with a sample of 150 independent retailers in Sana'a City, a questionnaire has been distributed, etch one represents the opinion of one independent retailer, and only 102 questionnaire were retrieved. The researcher founds that the Retailer is not yet qualified in terms of Experience and the Ability to shape Consumer trends, and he form the consumer trends only by providing the Domestic Goods in his store, and the Advice he offered to consumers are moving toward the similar foreign goods by 76% through its focus on quality and profit margin and Former Consumers Desire. it also appeared that the profit margin for domestic goods does not stimulate the independent retailer to adopt it and to push for the formation of consumer trend toward it. The researcher recommends to the retailers to train and specialize in the area of independent retailing through courses or by study in Marketing specialized institutes, and recommends to the Yemeni domestic good Companies to support concessional goods product through producing the providing quality and desires required by the consumer as well as to support the retailer profit margin so he could form a trend the consumer toward it products.
Keywords: Retailers behavior; Consumer trends; Domestic goods; Yemen